Descartes' system of natural philosophy - Gaukroger, Stephen (Cambridge University Press, 2002)
Towards the end of his life, Descartes published the first four parts of a projected six-part work, The Principles of Philosophy. This was intended to be the definitive statement of his complete system of philosophy. Gaukroger examines the whole system, and reconstructs the last two parts from Descartes' other writings.